REPATRIASI PENGUNGSI SURIAH: PERUBAHAN KEBIJAKAN TURKI DALAM MERESPON KRISIS PENGUNGSI - Izzatinnisa, Izzatinnisa; Muhammad Yusra; Maryam Jamilah (Hubungan Internasional Universitas Andalas, 2022)
This study aim to explain the driving factor of Turkish foreign policy change to repatriation refugees of Syria in 2019. As the largest house country for refugees in the world since 2011, Turkey which inclined to be accommodating in implementing the policy towards refugees, suddenly changed to plan repatriation of refugees that began in August 2019. The research method is qualitative with descriptive approach. Base on the concept, this study found that only two factors can explain the driving factor of Turkish foreign policy change to repatriation refugees of Syria, there are in domestic factors such us the government system changed from parlementary system to presidential system, the decrease influence of AK Parti in Turkish society, and negative sentiment between Turkish and refugees. Meanwhile in international factors such us there has friction relationship between Turkey and Rusia to solve Syrian conflict, degradation of cooperation commitment between EU and Turkey, and economic barrier between Turkey and US